A Complete Capital Model involving Heterogeneous Capital Goods - Samuelson, Paul A.; Solow, Robert M. (Quarterly Journal of Economics, 1956)
I. Introduction and review, 537. — II. Many-goods model, 539. — III. Euler necessary conditions, 541. — IV. Case of satiated production, 544. — V. Physical analogy of small vibrations, 547. — VI. Case of utility satiation, 549. — VII. Practical computation, 553. — VIII. Hamiltonian formulation, 554. — IX. Pay-off in terms of initial state, 559. — X. Conclusion, 561.